Effects of Red Galangal Rhizome Extract (Alpinia purpurata) as an Inhibitor of Staphylococcus aureus Bacterial Biofilm - Sri Winarsih; Ardian Rizal; Ratu, Estyka (Eureka Herba Indonesia, 2023)
Staphylococcus aureus is a type of bacteria that causes infection through the virulence mechanism of biofilm formation, namely forming a layer by removing the matrix as a form of defense from the immune system and from antibacterial agents. This bacterium makes it very easy to form biofilms, thereby reducing the effectiveness of therapy with antibiotics. Red galangal is a spice plant that grows a lot in Indonesia. It is known to contain flavonoids, tannins, and terpenoids, which are thought to have activity in inhibiting biofilm formation. This study aimed to determine the effect of red galangal rhizome extract in inhibiting the formation of biofilms of Staphylococcus aureus bacteria. The method used is the test tube method using crystal violet dye. The results of the tube test method were photographed and quantified into the mean gray value (MGV) found in the Adobe Photoshop CS6 application. The thicker the biofilm is indicated by the lower the MGV value. Red galangal extract was obtained by maceration using 96% ethanol solvent, while the extract concentrations for treatment were 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56%, and 0%. The results of statistical analysis showed that the higher the concentration of the extract, the thinner the biofilm ring formed (Pearson correlation, r = -0.980, p = 0.000). In conclusion, the ethanol extract of red galangal rhizome has the potential to inhibit Staphylococcus aureus biofilm formation with minimal biofilm inhibition at a concentration of 12.5%.